CFD Simulations to Study Parameters Affecting Gas Explosion Venting in Compressor Compartments. (11th December 2017) - Cen, Kang; Song, Bin; Huang, Yan; Wang, Qingsheng
Abstract : In this work, a series of vented explosions in a typical compressor compartment are simulated using FLACS code to analyze the explosion venting characteristics. The effects of relevant parameters on the pressure peaks (i.e., overpressure and negative pressure) are also numerically investigated, including vent area ratio of the compressor compartment, vent activation pressure, mass per unit area of vent panels, and volume blockage ratio of obstacles. In addition, the orthogonal experiment design and improved grey relational analysis are implemented to evaluate the impact degree of these relevant parameters. The results show that the pressure peaks decrease with the increase of vent area ratio. There is an approximately linearly increasing relationship between the pressure peaks and the vent activation pressure. The pressure peaks increase with the mass per unit area of vent panels. The pressure peaks increase with the volume blockage ratio of obstacles. Based on the grey relational grade values, the effects of these relevant parameters on the overpressure peak are ranked as follows: volume blockage ratio of obstacles > vent activation pressure > vent area ratio > mass per unit area of vent panels. These achievements provide effective guidance for the venting safety design of gas compressor compartments.